KEMAMPUAN PELATIHAN PASAR MODAL MEMODERASI PENGARUH PENGETAHUAN INVESTASI DAN PENGHASILAN PADA MINAT BERINVESTASI MAHASISWA - Merawati, Luh Komang; Semara Putra, I Putu Mega Juli (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 10 No 2 (2015))
The aim of the study is to investigate the influence of investment knowledge and income on the students’ intention to invest their money in capital market, where capital markets training variable as moderating variable. In order to achieve the goal of the study, respondents are student of Faculty of Economics- University of Mahasaraswati’s in Denpasar. Using purposive sampling technique, data were analyzed using multiple regression analysis with interaction to test hypotheses. The result of the study shows that investment knowledge and income have a positive effect on students’ intention to invest their capital in the capital market. In contrast, according to the interaction test of capital market training as moderating variable does not show a significant effect. It means that capital market training unable to strengthen or weaken the relationship investment knowledge and incomes on students’ intention to invest.
Keywords: investment knowledge, capital market training, incomes and students’ intention to invest